Differences in Age and Body Mass Index of Women with Polycystic Ovary Syndrome Attending in Vitro Fertilization (IVF) Program - Roselina Panghiyangani; Husnul Khatimah; Dwi Anita Suryandari; Budi Wiweko; Mala Kurniati (Berkala Kedokteran, 2019)
Abstract: Nutritional status in this case BMI in women is very important in relation to infertility problems in women of reproductive age. Polycystic ovary syndrome (PCOS), is a reproductive problem with hormonal disorders. Infertility Female with PCOS is associated with anovulation, high LH and hyperandrogenism. The purpose of this study was to analyze differences in age and body mass index (BMI) of PCOS women undergoing in vitro fertilization (IVF). This was an observational analytic study. The subjects of the study were women aged 30-40 years who undergoing IVF-assisted fertilization program at Yasmin Clinic - RSCM Kencana who was diagnosed as PCOS. As a comparison are women 30-40 years who have infertility problems but not PCOS  who underwent IVF-assisted fertilization program. Women diagnosed with PCOS based on the Rotterdam 2003 consensus definition, and reinforced with ultrasound examinations that show polycystic ovary symptoms. Diagnosis is performed by a specialist in Obstetrics and Gynecology. Age data is taken from medical record and IMT data is calculated based on formula body weight/height2. Data analysis was done by unpaired t test. Mean age of study subjects: 32.21 ± 0.99 years female PCOS and 32.80 ± 0.516 years of non-PCOS group of women, unpaired t-test results were not significantly different (p> 0.05). Mass Index PCOS group 24.425 ± 0.585 Kg/m2 and 22.840 ± 0.494 Kg/m2 non-PCOS group, unpaired t-test results were significantly different (p <0.05). Conclusion of this research was in the PCOS women group had significantly higher BMI rates than the group non PCOS woman.